Factors affecting the intention to become an entrepreneur: A study from Bangladeshi business graduates' perspective - Kabir, SM; Haque, A. K. M. Ahasanul; Sarwar, Abdullah (International Journal of Engineering and Information Systems (IJEAIS), 2017)
The current stage of entrepreneurial culture in Bangladesh encourages rethinking about the content and approach of teaching in entrepreneurship education. Therefore, this study aimed at identifying the factors influencing Bangladeshi graduates’ intention toward becoming entrepreneurs. A sample of 387 business graduate students was selected randomly from both private and public universities located in Dhaka and Rajshahi. Partial Least Squares Structural Equation Modeling (PLSSEM) has been employed to test the structural relationship among variables that influence respondent’s entrepreneurial intention. This study has found that entrepreneurial education will provide skills and knowledge that might help the students to change their typical mind-set from searching job to creating jobs. Hence, focusing on developing entrepreneurial mind through education will have importance for the development of entrepreneurial culture as well as for the sustainable socioeconomic development in Bangladesh.